Void Formation and Crack Propagation in a Cr–Mn–N Metastable Austenitic Stainless Steel During Bending. Issue 3 (29th November 2022) - Kamali, Hamidreza; Xie, Haibo; Bi, Hongyun; Chang, E; Xu, Haigang; Yu, Haifeng; Jiang, Zhengyi; Gazder, Azdiar A.
Abstract : Microstructure evolution via deformation‐induced martensitic transformation, void formation, and crack propagation is investigated in a metastable austenitic Cr–Mn–N stainless steel for up to 90° bending using a combination of electron backscattering diffraction and parent grain reconstruction. Stress–strain heterogeneity and stress triaxiality studied using finite‐element analysis reveal that the inner and outer radii are in approximately uniaxial compressive and tensile stress states, respectively, with the outer radius showing higher values for von Mises and principal stresses and equivalent strain. Voids are observed at both austenite/ α ′‐martensite and α ′/ α ′‐martensite interfaces. Parent grain reconstruction applied to the 90° bending sample reveal that the cracks at α ′/ α ′‐martensite interfaces tend to propagate predominantly along intergranular parent austenite grain boundaries. It is also found that both intragranular and intergranular cracks in parent austenite tend to propagate between α ′‐martensite child–child grains comprising the same crystallographic packets. This is the first study of its kind to comprehensively show this phenomenon. A representative example of intergranular crack propagation within a ⟨ 110 ⟩ ‖normal direction (ND)‐oriented parent austenite grain is also demonstrated. Abstract : Void formation and crack propagation are studied in transformation‐induced plasticity (TRIP) and twinning‐induced plasticity (TWIP) steel during bending. Void formation sites are identified. Cracking conquest are observed at austenite/ α ′‐martensite interfaces due to martensitic transformation. Intragranular and intergranular cracks in parent austenite tend to propagate between α child–child grains comprising the same crystallographic packets.